2012
DOI: 10.3389/fphys.2012.00431
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of the crustacean gill: osmotic/ionic regulation, acid-base balance, ammonia excretion, and bioaccumulation of toxic metals

Abstract: The crustacean gill is a multi-functional organ, and it is the site of a number of physiological processes, including ion transport, which is the basis for hemolymph osmoregulation; acid-base balance; and ammonia excretion. The gill is also the site by which many toxic metals are taken up by aquatic crustaceans, and thus it plays an important role in the toxicology of these species. This review provides a comprehensive overview of the ecology, physiology, biochemistry, and molecular biology of the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
286
0
20

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 366 publications
(336 citation statements)
references
References 360 publications
(546 reference statements)
13
286
0
20
Order By: Relevance
“…Therefore, it is a potential site for large, diffusive losses of ions through paracellular (intercellular) pathways. A considerable amount of energy is used for active uptake of salts to allow hyperosmoregulation in DSW (Onken and Siebers, 1992;Lucu and Flik, 1999;Henry et al, 2012). We have demonstrated a small decrease of conductance under severe 1.6 mg O 2 hypoxia, when > 95% of Isc was inhibited by hypoxia.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, it is a potential site for large, diffusive losses of ions through paracellular (intercellular) pathways. A considerable amount of energy is used for active uptake of salts to allow hyperosmoregulation in DSW (Onken and Siebers, 1992;Lucu and Flik, 1999;Henry et al, 2012). We have demonstrated a small decrease of conductance under severe 1.6 mg O 2 hypoxia, when > 95% of Isc was inhibited by hypoxia.…”
mentioning
confidence: 83%
“…Furthermore, a substantial increase in oxygen consumption (Piller et al, 1985;Lucu and Pavičić, 1985) in the posterior gills of the crabs Callinectes and Carcinus after acclimation to 10-20 ppt DSW indicate an increased gill metabolism. Thus, in these crabs acclimated in DSW activity of Na + ,K + -ATPase is increased in posterior gills specialized for active ion uptake (Towle et al, 1976;Holliday, 1985;Lucu and Flik, 1999;Lovett et al, 2007;Tsai and Lin, 2007;Henry et al, 2012). Increased diffusion distance may reduce the ability to take up oxygen and reduce loss of ions from the hemolymph and thus the cost of ion regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…70 Further studies identified the gill as the most important site of osmotic regulation and discovered transporters and mechanisms that allowed some crustacean species to actively regulate extracellular osmolarity against steep osmotic gradients. 71,72 Although the existence of the NKA located in branchial epithelia of the cuttlefish Sepia officinalis was revealed using enzymatic assays in the late 70 ties, its role in branchial ion regulation was less well understood. 39 Molecular characterization of the cephalopod NKA using full length clones of the squid (Loligo opalescens and L. pealeii) NKA revealed fundamental structural differences between osmo-conformers like cephalopods and vertebrates that are capable of maintaining hypo-osmotic conditions in marine environments.…”
Section: The Ph Regulatory Machinerymentioning
confidence: 99%
“…Third, as crustacean gills are multi-functional, not only serving as respiratory gas-exchange organs but also engaging in active ion transport required for ionic and osmotic regulation (Pequeux, 1995;Lingot et al, 2000;Brooks and Mills, 2003;Freire et al, 2008;Henry et al, 2012), gill SA should be smaller in aquatic habitats with high versus low ion concentrations (conductivity), because a less steep ionic gradient between the inside and outside of the body entails a reduced rate of ion loss and thus a lesser demand for compensating ion uptake (assuming that ion uptake per unit gill area is invariant). The lower metabolic demand of ionic regulation in water with high ion concentrations (Sutcliffe, 1984;Glazier and Sparks, 1997) should also require less oxygen uptake, again favoring smaller gills.…”
Section: Introductionmentioning
confidence: 99%